The technical capacity of local governments in Zio1 (Togo) and Zou (Benin) to propose solutions to climate risks - Houndjo, Komlan; Kpotchou, Koffi (Edelweiss Applied Science and Technology, 2024)
Solutions to climate risks in municipalities require the development and implementation of specific policies and measures aimed at providing solutions to climate risks, promoting better management of environmental and energy resources, and strengthening the resilience of poor and marginalized populations to climate change. However, municipalities in West Africa, and in particular the municipality of Zio1 (Togo) and those of Zou (Benin), have little technical capacity to conduct climate policies autonomously at local level. This article aims to examine the technical capacity of the municipalities of Zio1 and Zou to propose solutions to climate risks. The work is based on the hypothesis that the technical capacity of municipalities limits their search for solutions to the risks caused by climate change. To verify this, a survey was carried out from September to November 2023 with 449 people aged 18 and over, altogether in Zio1 and Zou municipalities. The results show that municipalities have little technical capacity to take action on climate change at local level. This weakness is manifested by the lack of qualified human resources related to climate risks.